Patch and soil characteristics of pastures with water‐spreading banks and woody encroachment in semi‐arid Australia. (18th March 2013) - Smith, Rhiannon; Tighe, Matthew; Reid, Nick; Briggs, Sue; Wilson, Brian
Summary Water‐spreading banks are used in semi‐arid areas such as the Cobar pediplain in western New South Wales, Australia to encourage pasture growth, often after removal of woody encroachment. We studied the arrangement of bare inter‐patches and vegetated patches, and associated surface soil variables, in three pastures following installation of water‐spreading banks (2, 15, 38 years ago) and in an area of woody encroachment near Cobar. The aims of the study were as follows: (i) to determine the number and percent area of inter‐patches and vegetated patches, and associated surface soil variables at the three pasture sites and at the woody encroachment site and (ii) by inference, explore effects of establishing water‐spreading banks and pasture following removal of woody encroachment on these factors, to understand the role of water‐spreading banks as a management tool. The percent area of inter‐patches in pasture with 38‐year‐old water‐spreading banks was much lower, and the percent area of medium‐vegetated patches (but not of well‐vegetated patches) was substantially higher, than in the woody encroachment. Differences in soil carbon and nitrogen between the sites were related to their percent areas of inter‐patches and vegetated patches. The results suggest that the mosaic of bare inter‐patches and vegetated patches changes over time after clearing of woody encroachment and establishment of pasture with water‐spreading banks, from many large inter‐patches to a few small inter‐patches, and from small to large medium‐vegetated patches. Water‐spreading banks are a useful management tool in these landscapes because of their benefits for landscape function, that is, bare areas become less connected, the percent area of moderately vegetated patches increases, and soil carbon builds up with time following their installation.